2018
DOI: 10.5965/1982615x11212018126
|View full text |Cite
|
Sign up to set email alerts
|

Renda de Bilros: estudo de pontos tecidos nas regiões Nordeste e Sul do Brasil

Abstract: Renda de Bilros: estudo de pontos tecidos nas regiões Nordeste e Sul do Brasil Bobbin Lace: study of the stitches woven in the northeastern and southern regions of Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…This study highlights that within the Pronaf B typology, some farmers face worse socio-economic and productive conditions and rely on Pronaf for their subsistence near the poverty threshold. Silva et al (2007) found that Pronaf B farmers in the poorest areas of the greater Northeast region face more challenges in accessing credit compared to Pronaf B farmers in the poorest areas of the Southern of Brazil. This aligns with the findings in Table 6.…”
Section: Impacts Of Pronaf Access: Typology Family Farming (Ff) -Pron...mentioning
confidence: 96%
“…This study highlights that within the Pronaf B typology, some farmers face worse socio-economic and productive conditions and rely on Pronaf for their subsistence near the poverty threshold. Silva et al (2007) found that Pronaf B farmers in the poorest areas of the greater Northeast region face more challenges in accessing credit compared to Pronaf B farmers in the poorest areas of the Southern of Brazil. This aligns with the findings in Table 6.…”
Section: Impacts Of Pronaf Access: Typology Family Farming (Ff) -Pron...mentioning
confidence: 96%
“…Ele surge, na narrativa oficial, como uma esperança de cidadania, introdução social e econômica.Após a criação do Pronaf, algumas pesquisastais como o relatório feito pelo Instituto de Pesquisa Econômica Aplicada(2013), assim como os trabalhos de Lopes, Lowery e Peroba (2016) eDuarte et al (2017), por exemplomostraram a importância desse programa para o desenvolvimento do meio rural, sobretudo no que diz respeito à impulsão da produção, ao estímulo à utilização de insumos modernos e ao auxílio à adoção de novas tecnologias, todos levando à melhoria da eficiência das unidades produtivas. Mas há também literatura questionando a concentração e a má distribuição dos recursos do Pronaf entre as regiões e entre os produtores familiares(MATTEI et al, 2007;CORREA;NEDER,…”
unclassified